Optimizing Human Resource Practices to Enhance Global Competitiveness in Higher Education - Supriyono, Eko; Wijoyo, Adhistyo (International Journal of Integrative Sciences, 2024)
Amidst the period of globalization, higher education institutions are confronted with mounting pressure to compete on a worldwide level. This rivalry requires the attraction of students, faculty, and researchers with various international backgrounds and the production of high-quality, influential research. Efficient human resource management (HRM) is crucial in this particular situation. This study investigates the strategic HRM approaches that can improve the global competitiveness of higher education institutions. The research use qualitative methodologies, such as in-depth interviews and thematic analysis, to identify crucial human resource management (HRM) strategies. These strategies encompass strategic recruitment, ongoing professional development, efficient performance management, employee engagement, and leadership development. Furthermore, the study offers practical suggestions for institutions to enhance the quality of their research and education. These recommendations include engaging in strategic planning to improve academic development, encouraging student participation in research, forming partnerships with industries, investing in research infrastructure, and creating comprehensive training programs. By maximizing these human resource management (HRM) techniques, educational institutions can more effectively adjust to global difficulties, improve their international reputation, and make substantial contributions to scientific and educational progress